2019
DOI: 10.5812/ijpbs.12498
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effectiveness of Auricular Acupuncture in Suicidal Ideation and Cortisol Level in Dysthymic Patients with Comorbid Opiate Use Disorders Enrolled in Methadone Maintenance Treatment: A Randomized, Double-Blind, Sham-Controlled Trial

Abstract: Background: Suicide is one of the leading causes of death around the world. The hypothalamic-pituitary-adrenal (HPA) axis disorder is involved in the pathophysiology of suicidal behavior. Acupuncture by regulating the activity of the HPA axis could regulate the secretion of cortisol. Objectives: This study aimed to evaluate the effectiveness of auricular acupuncture in the reduction of cortisol level and suicidal ideation in dysthymic patients with comorbid opiate use disorders enrolled in methadone maintenanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(28 citation statements)
references
References 15 publications
2
26
0
Order By: Relevance
“…The secondary results of this study showed that acupuncture reduced the severity of suicidal ideation. These results are consistent with the findings of another study (5). In line with the findings of the present study, electro-acupuncture by modulating the HPA axis function and enhancing the activity of the hippocampus was associated with reduced symptoms of depression (8).…”
Section: Dear Editor-in-chiefsupporting
confidence: 94%
See 2 more Smart Citations
“…The secondary results of this study showed that acupuncture reduced the severity of suicidal ideation. These results are consistent with the findings of another study (5). In line with the findings of the present study, electro-acupuncture by modulating the HPA axis function and enhancing the activity of the hippocampus was associated with reduced symptoms of depression (8).…”
Section: Dear Editor-in-chiefsupporting
confidence: 94%
“…Secondary outcomes also showed that acupuncture was associated with a reduction in suicidal ideation. In line with the primary outcomes of the present research, the use of acupuncture through promoting adrenocorticotropic hormone and the secretion of plasma cortisol led to regulation of HPA axis activity in the mice with asthma (4, 5, 7).…”
Section: Dear Editor-in-chiefsupporting
confidence: 81%
See 1 more Smart Citation
“…Overall, 24 methadone patients with the diagnosis of depression received either auricular acupuncture (AA) or sham acupuncture during four weeks. Interestingly, participants in the treatment group showed significantly better results than the control group in term of reduced suicidal ideation (10).…”
mentioning
confidence: 91%
“…In a recent published article in your journal, "evaluation of the effectiveness of auricular acupuncture in suicidal ideation and cortisol level in dysthymic patients with comorbid opiate use disorder enrolled in methadone maintenance treatment: a randomized double-blind, sham controlled trial", authors have suggested a new intervention to treat suicidal ideation in methadone therapy in Iran (10). Overall, 24 methadone patients with the diagnosis of depression received either auricular acupuncture (AA) or sham acupuncture during four weeks.…”
mentioning
confidence: 99%